Impact of Occupational Hazards on Pulmonary Function among Selected Textile Industry Workers in Tirupur - K. Karuppusamy Shanmukapriya; V. Premala Priyadharsini (Universitas Airlangga, 2025)
Introduction: Occupational respiratory diseases represent a global public health issue especially in textile Industry. Exposure to cotton dust is a major contributor, leading to respiratory issues such as coughing, phlegm, wheezing, shortness of breath, chest tightness, chronic bronchitis, and byssinosis, all of which cause severe pulmonary illness. The objective is to assess the pulmonary function of selected textile industry workers of Tirupur, Tamil Nadu. Method: Using Crochan’s Formula 656 textile workers from six textile industries of Tirupur (5) and Coimbatore (1) were selected using purposive sampling. The current paper focuses on 160 workers of both the sex (male 124, female 36) working not less than 5-years in the textile industry. A mixed research design (Qualitative and Quantitative) was used. A Qualitative analysis on perception of occupational Hazard and impact on the respiratory illness among the textile industry worker was done among 38 respondents. As part of quantitative research, the demographic details, anthropometric measurements, nature of work, pulmonary function and lifestyle practices such physical activity, smoking, pan chewing and alcohol consumption of the worker were elicited using a validated interview schedule. Using Flow Measuring Spirometer (Helios_v3.2.56) the pulmonary function was tested for Forced Expiratory Volume in the first second (FEV1), Forced Vital Capacity (FVC), FEV1/FVC ratio according to the guidelines of American Thoracic Society. Result: Sneezing was common symptom experienced followed by allergy, cough and irritation. Among the 160 workers interviewed 33% of the textile workers fell within the age group 20-30 years. The mean BMI was found to be similar for both male (23.39±4.2) and female workers (23.4±4.6). The workers had poor pulmonary function with their FEV1, FVC, and FEV1/FVC ratios lower than the reference value significant at 1% level (p<0.0001). A higher prevalence of early airway obstruction in females (44%) was observed compared to males (10%). Mild restriction (<80) was observed in 13% of males and 14% of females, while moderate restriction (<64) was reported in 7% of males and 14% of females respectively. Conclusion: Prolonged exposure to cotton dust may attribute to respiratory symptoms such as coughing, wheezing, and chest tightness.